1H NMR Chemosensing of Potassium Ions Enabled by Guest‐Induced Selectivity Switch of a Gold Nanoparticle/Crown Ether Nanoreceptor. Issue 10 (22nd August 2019) - Sun, Xiaohuan; Rosa‐Gastaldo, Daniele; De Biasi, Federico; Rastrelli, Federico; Mancin, Fabrizio
Abstract: Invited for this month's cover is the group of Prof. Fabrizio Mancin from the University of Padova, Italy. The cover picture shows an 18‐crown‐6‐functionalized gold nanoparticle that switches its molecular recognition preference from organic cations to organic anions in the presence of potassium ions, thus allowing 1 H NMR sensing of potassium. Read the full text of the article at 10.1002/cplu.201900028 . Abstract : "We think that the self‐organized and multifunctional nature of these nanoparticles offer a straightforward shortcut for the realization of chemical systems with the complexity and behavior similar to that of proteins." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.201900028 ).